2019
DOI: 10.1002/ccr3.2281
|View full text |Cite
|
Sign up to set email alerts
|

False positive bladder scan in ascites with anuria

Abstract: Urinary retention is commonly diagnosed based on history and examination along with bedside bladder scan. However, in patients where clinical examination is unreliable (patients with obesity, anasarca, and ascites) and diagnosis is uncertain, the bladder scan findings should be interpreted with caution and definitive imaging is mandatory before further intervention is instituted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Previous studies suggested strong correlations between the volumes measured by bladder scan and the CT contoured volume in prostate radiotherapy patients. 24,28 Since the bladder scan findings are reported to be influenced by the presence of ascites 29 and possibly in highly obese patients. 30 Therefore, we evaluated ascites by TPCT and obesity by the body mass index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested strong correlations between the volumes measured by bladder scan and the CT contoured volume in prostate radiotherapy patients. 24,28 Since the bladder scan findings are reported to be influenced by the presence of ascites 29 and possibly in highly obese patients. 30 Therefore, we evaluated ascites by TPCT and obesity by the body mass index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…The nominal accuracy of the device is ± 15%. Previous studies suggest strong correlations between the volumes measured by bladder scan and the CT contoured volume in prostate radiotherapy patients [17,20], however, bladder scan ndings are reported to be unreliable in obese and ascites patients [21], and we determined obesity by body mass index (BMI) and ascites by RT-CT. All UV measurements were performed by the same person.…”
Section: Urinary Volume (Uv) Measurementsmentioning
confidence: 99%